Histological Studies on the Tongue of Adult White Leghorn Hens - Shikha Saini (Indian Journal of Veterinary Anatomy, 2022)
The present study evaluated the histological characteristics of the tongue in twenty adult White Leghorn hens. The dorsal surface of the apex, body, caudal lingual papillae and root were lined by the stratified squamous non-keratinized epithelium. The ventral surfaces of the body and root were lined by stratified squamous nonkeratinized epithelium whereas, that of the apex was lined by the stratified squamous keratinized epithelium. The dense fibrous sub-epithelial connective tissue was composed of collagen, and a few elastic and reticular fibres along with blood vessels, nerve bundles and small bundles of lingual muscles. The mucosa of the body and root was characterized by the presence of solitary lymphoid nodules. The hyoid apparatus was embedded throughout the length of the tongue and it was comprised of hyaline cartilage in the rostral part and got ossified towards the caudal part of the tongue. The papillary crest appeared as an evagination of the dorsal lingual epithelium at the body-root junction. The anterior lingual glands were present in the body whereas; posterior lingual glands were present in the region of caudal lingual papillae and the root.